RELEVANSI KEBIASAAN PRAETER LEGEM DENGAN TOROK DALAM PERAYAAN EKARISTI DI MANGGARAI - Jama, Andreas (Jurnal Euntes, 2024)
This research pays attention to the practice of torok or kepok carried out by Catholics in Manggarai in the celebration of the Eucharist or holy mass. Indeed, the practice of torok or kepok is not done every time the Eucharist is celebrated. There are certain times of Eucharistic celebrations, for example in major celebrations or during thanksgiving masses, torok or kepok becomes a crucial and absolute thing to do. This has become a custom for Catholics in Manggarai. Thus, the purpose of this study is to find out about the relationship between the practice of torok or kepok in the celebration of the Eucharist with ecclesiastical law or canon law. The methodology used in this research is a literature study, where the author searches and collects information related to this research from various sources such as books, journals, newspapers and the internet. Then, the author correlates it with customs in the context of ecclesiastical law or canon law. Some of these customs are secundum legem, praeter legem, and contra legem. This research found that torok in the Eucharistic celebration practiced by Catholics in Manggarai is an example or form of praeter legem custom. This means that the practice of torok in the Eucharistic celebration is a custom that is outside the provisions of universal (canonical or ecclesiastical) law. In other words, it is not regulated or does not exist in the general law.